Surface integrity evaluation on titanium alloy after EDM machining using different graphite electrodes - Mat Jusoh, Mazlan (2010)
The quality of an EDM product is usually evaluated in terms of its surface integrity, having these specific characteristic like the surface roughness, existence of surface cracks and residual stresses. Many process variables affect the surface integrity such as Pulse Duration, Peak Current, Open Gap Voltage and electrode Polarity. Other than that, material properties of the tool electrode, workpiece and dielectric liquid in fact even the size of the electrode affects the surface integrity. The purposes of this study are to investigate the influences of the parameters involved in EDM especially on the machining characteristics, namely recast layer (white layer), heat affected zone, surface topography, micro cracks and voids on the titanium alloys using POCO 3 and POCO C3 as an electrode. The specimens were examined using Optical Microscope (Zeiss), Scanning Electron Microscope (SEM) XL-40 with EDAX analysis and X-Ray Diffraction (Siemens - D5000). The Full Factorial Design of Experiment (DOE) approach was used to analyze the effect of each parameter such as Pulse ON (ON), Pulse OFF (OFF), Peak Current (IP) and Servo Voltage (SV) on the EDM machining characteristics. In general, the Peak Current and Pulse ON have the most significant effect to the responses studied. EDMed with POCO 3 gives the better results compared to POCO C3 in term of recast layer thickness and in contrary with the HAZ thickness. The mathematical models for average recast layer thickness and average heat affected zone thickness were developed to predict the effects within the factors investigated.